The relative efficiency of schizophrenia health care systems: an international comparison using data envelopment analysis. (2nd October 2020) - Weatherall, James; Simonsen, Jacob; Odlaug, Brian L.
Abstract: Aim: To compare the health economic efficiency of health care systems across nations, within the area of schizophrenia, using a data envelopment analysis (DEA) approach. Methods: The DEA was performed using countries as decision-making units, schizophrenia disease investment (cost of disease as a percentage of total health care expenditure) as the input, and disability-adjusted life years (DALYs) per patient due to schizophrenia as the output. Data were obtained from the Global Burden of Disease 2017 study, the World Bank Group, and a literature search of the PubMed database. Results: Data were obtained for 44 countries; of these, 34 had complete data and were included in the DEA. Disease investment (percentage of total health care expenditure) ranged from 1.11 in Switzerland to 6.73 in Thailand. DALYs per patient ranged from 0.621 in Lithuania to 0.651 in Malaysia. According to the DEA, countries with the most efficient schizophrenia health care were Lithuania, Norway, Switzerland and the US (all with efficiency score 1.000). The least efficient countries were Malaysia (0.955), China (0.959) and Thailand (0.965). Limitations: DEA findings depend on the countries and variables that are included in the dataset. Conclusions: In this international DEA, despite the difference in schizophrenia disease investment across countries, there was little difference in output as measured by DALYs per patient. Potentially, Lithuania, Norway, Switzerland and the US should be considered 'benchmark' countries by policy makers, thereby providing useful information to countries with less efficient systems.